Outcome of Orchidopexy in Spigelian Hernia-Undescended Testis Syndrome - Taha, Abdulrahman (Cureus, 2021)
Spigelian hernia-undescended testes (SH-UDT) syndrome is a rare disorder, with only 57 cases reported in the literature. The presentation can be asymptomatic or symptomatic in the form of pain, tenderness, or a lump. We present a case of a 50-day-old boy with SH-UDT syndrome. The patient presented with signs and symptoms of acute intestinal obstruction. Exploration confirmed a Spigelian hernia containing small bowel loops and right undescended testis. Orchidopexy was done after ligation of the hernial sac. A follow-up visit after two years revealed right testicular atrophy.